Genetic Encoding of Bicyclononynes and trans-Cyclooctenes for Site-Specific Protein Labeling in Vitro and in Live Mammalian Cells via Rapid Fluorogenic Diels–Alder Reactions - Lang, Kathrin (American Chemical Society, 2012)
[Image: see text] Rapid, site-specific labeling of proteins with diverse probes remains an outstanding challenge for chemical biologists. Enzyme-mediated labeling approaches may be rapid but use protein or peptide fusions that introduce perturbations into the protein under study and may limit the sites that can be labeled, while many “bioorthogonal” reactions for which a component can be genetically encoded are too slow to effect quantitative site-specific labeling of proteins on a time scale that is useful for studying many biological processes. We report a fluorogenic reaction between bicyclo[6.1.0]non-4-yn-9-ylmethanol (BCN) and tetrazines that is 3–7 orders of magnitude faster than many bioorthogonal reactions. Unlike the reactions of strained alkenes, including trans-cyclooctenes and norbornenes, with tetrazines, the BCN–tetrazine reaction gives a single product of defined stereochemistry. We have discovered aminoacyl-tRNA synthetase/tRNA pairs for the efficient site-specific incorporation of a BCN-containing amino acid, 1, and a trans-cyclooctene-containing amino acid 2 (which also reacts extremely rapidly with tetrazines) into proteins expressed in Escherichia coli and mammalian cells. We demonstrate the rapid fluorogenic labeling of proteins containing 1 and 2 in vitro, in E. coli, and in live mammalian cells. These approaches may be extended to site-specific protein labeling in animals, and we anticipate that they will have a broad impact on labeling and imaging studies.